Modulation of empathic abilities by the interplay between estrogen receptors and arginine vasopressin - Rui Du; Ting Liang; Guofang Lu (Neuroscience Research, 2025)
This review examines the complex interactions between estrogen receptors α and β (ERα and ERβ) and arginine vasopressin (AVP), delving into their significant roles in modulating empathy, a critical psychological component in human social dynamics. Empathy, integrating affective and cognitive elements, is anchored in neural regions like the amygdala and prefrontal cortex. ERα and ERβ, pivotal in estrogen regulation, influence neurotransmitter dynamics and neural network activities, crucial for empathic development. AVP, key in regulating water balance, blood pressure, and social behaviors, interplays with these receptors, profoundly impacting empathic responses. The study highlights that ERα predominantly enhances empathy, especially affective empathy, by stimulating AVP synthesis and release. In contrast, ERβ may diminish empathy in certain contexts by suppressing AVP expression and activity. The intricate interplay, homeostatic balance, and mutual conversion between ERα and ERβ in AVP regulation are identified as challenging yet crucial areas for future research. These findings provide essential insights into the neurobiological underpinnings of empathy, offering new avenues for therapeutic interventions in social cognitive disorders and emotional dysregulation.